2019
DOI: 10.1093/mnras/stz3195
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a 260 pc wide, 35-Myr-old filamentary relic of star formation

Abstract: Several recent studies have shown that the Vela OB2 region hosts a complex constellation of sub-populations with ages in the range 10 to 50 Myr. Such populations might represent the best example of the outcome of clustered star formation in Giant Molecular clouds (GMC). We use Gaia DR2 data over an area of 40 deg radius around the open cluster Collinder 135 to extend the study of the stellar populations of the Vela OB2 region over an area of several hundreds of parsecs on sky. Detailed clustering algorithms co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 38 publications
2
39
0
1
Order By: Relevance
“…This observational evidence highlights that the observed coronae could be a consequence of the filamentary, highly substructured nature of starforming regions. In reference to Beccari et al (2020), we note that NGC 2547 is part of their identified structure (see also Cantat-Gaudin et al 2019a,b). Our analysis of this cluster, however, does not produce unambiguous evidence that the cluster is embedded in a larger structure.…”
Section: Origin Of the Coronaementioning
confidence: 55%
“…This observational evidence highlights that the observed coronae could be a consequence of the filamentary, highly substructured nature of starforming regions. In reference to Beccari et al (2020), we note that NGC 2547 is part of their identified structure (see also Cantat-Gaudin et al 2019a,b). Our analysis of this cluster, however, does not produce unambiguous evidence that the cluster is embedded in a larger structure.…”
Section: Origin Of the Coronaementioning
confidence: 55%
“…We utilize densitybased clustering (Ester et al 1996;Kriegel et al 2011) to the data set. It is a general statistical method that recently has begun to be applied to classify astronomical sources in a multidimensional data space (e.g., Beccari et al 2018Beccari et al , 2020Jerabkova et al 2019). This method can identify clusters in a multidimensional space not only for their crests but also for their spatial extent, without assuming that their underlying spatial structures are filamentary or clumpy.…”
Section: Appendix D Identification Of Emission Features Using Densitymentioning
confidence: 99%
“…Cr 135 and UBC 7 are located at a distance of approximately 300 pc in the Vela-Puppis star formation region (245 deg l 265 deg, −15 deg b −5 deg), which was recently thoroughly investigated with respect to its large-scale structure and kinematics using Gaia DR2 data (Cantat-Gaudin et al 2019a,b;Beccari et al 2020). In particular, the region at distances between 250 and 500 pc hosts several young open clusters divided into groups of similar age.…”
Section: Characterising Cr 135 and Ubc 7 With Gaia Dr2mentioning
confidence: 99%
“…The oldest group (30-50 Myr according to different authors, e.g. Cantat-Gaudin et al 2019a;Beccari et al 2020) includes Cr 135 and UBC 7.…”
Section: Characterising Cr 135 and Ubc 7 With Gaia Dr2mentioning
confidence: 99%
See 1 more Smart Citation